القصاص في القتل بين الشريعة الإسلامية والقانونين الليبي والماليزي دراسة مقارنة - AbdulKarem Mohd Ali Dannoni (Universiti Sains Islam Malaysia, 2024)
The Quran had prescribed the principles of punishment, and oblige believers to follow the penalty as stated in Quran, where the evidences from Qura’n and Sunnah showed clear statements on this matter. The punishment represents justice. This research is limited to discuss the criminal studies for self-protection through Islamic jurisprudence and Libyan and Malaysian legislation. The significance of this research is based on considering the penalty and punishment as the best way to control murder and killing. The problem that will be discussed in this research is the spread of crimes and murder, neglecting to apply the penalty on criminals which leads to increase the effect of this phenomenon without any control, the study also discuss the protesting of secularists and human rights organizations on penalty of murder. The aim of this study is to introduce the principles of penalty on murder from the perspective of Shariah (Islamic legislation) and Law. The researcher used inductive and descriptive methodology to describe the problem statement of this study, also used the analytical approach, then comparative methodology. The main findings of this research is that scholars who suspect the purpose of penalty to murderers as the most severe penalties, where the main purpose is killing the murderer without looking to the mean. The scholars show that killing using psychological means is intentional murder. The study recommended that killing using psychological means is considered a semi-intentional murder, and this is more close to the principle of Islamic Shariah, and changing the Article 373 of Libyan Penal Code, which states that infanticide is done to protect the honor, and modify Article 375 of Penal Code that states to reduce the penalty on father, son, brother, who murdered a relative woman after discovering the act of adultery because of the violation of the Shariah (Islamic legislation).